Burden of Disease of COVID-19: Strengthening the Collaboration for National Studies - Pires, Sara Monteiro; Wyper, Grant M. A.; Wengler, Annelene; Peñalvo, José L.; Haneef, Romana; Moran, Declan; Cuschieri, Sarah; Redondo, Hernan G.; De Pauw, Robby; McDonald, Scott A.; Moon, Lynelle; Shedrawy, Jad; et al. (Frontiers in Public Health, 2022)
Objectives Quantifying the combined impact of morbidity and mortality is a key enabler to assessing the impact of COVID-19 across countries and within countries relative to other diseases, regions, or demographics. Differences in methods, data sources, and definitions of mortality due to COVID-19 may hamper comparisons. We describe efforts to support countries in estimating the national-level burden of COVID-19 using disability-adjusted life years (DALYs). Methods The European Burden of Disease Network developed a consensus methodology, as well as a range of capacity-building activities to support burden of COVID-19 studies. These activities have supported 11 national studies so far, with study periods between January 2020 and December 2021. Results National studies dealt with various data gaps and different assumptions were made to face knowledge gaps. Still, they delivered broadly comparable results that allow for interpretation of consistencies, as well as differences in the quantified direct health impact of the pandemic. The estimated burden of COVID-19 at national level in completed country-level studies ranged between 32 and nearly 2,000 DALYs per 100,000 inhabitants, and studies consistently estimated a large contribution of the mortality component to the burden, between around 1 and 5%.